2004
DOI: 10.1248/bpb.27.1814
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and in Vitro Antimicrobial Activities of the Essential Oils from Endemic Psiadia Species Growing in Mauritius

Abstract: Essential oils are among the secondary metabolites of higher plants. These fragrant compounds comprise volatile terpenes, sesquiterpenes as well as their derivatives. The antimicrobial attributes of essential oils have been recognized long ago but only recently it has been established scientifically. 1,2) Among the essential-oil bearing families are the Asteraceae (Compositae). This family is one of the largest plant family with over 1000 genera and 25000 species and growing in several different habitats. Many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 12 publications
(8 reference statements)
3
8
0
Order By: Relevance
“…It is noteworthy that the antibacterial activity of b-bisabolene described in the present study is in agreement with results reported by other groups showing that the activity of essential oils of other Asteraceae species against S. aureus is also due to this compound (Gouvinden-Soulange et al 2004;Simic et al 2005).…”
Section: Discussionsupporting
confidence: 93%
“…It is noteworthy that the antibacterial activity of b-bisabolene described in the present study is in agreement with results reported by other groups showing that the activity of essential oils of other Asteraceae species against S. aureus is also due to this compound (Gouvinden-Soulange et al 2004;Simic et al 2005).…”
Section: Discussionsupporting
confidence: 93%
“…There was no clear relationship across all highbush blueberry cultivars studied for volatiles emitted (both quantitative and qualitative differences) and resistance to anthracnose fruit rot. Except for 8-hydroxylinalool, all of the aldehydes and terpenes identified as evolving from the highbush blueberry samples in this study have been reported to have antifungal properties, although not necessarily against C. acutatum (Archbold et al, 1997;Azaz et al, 2002;Carson and Riley, 1995;Cavaleiro et al, 2006;Corbo et al, 2000;Fraternale et al, 2004;Govinden-Soulange et al, 2004;Himejima et al, 1992;Lanciotti et al, 1999;Peana et al, 1999;Plotto et al, 2003;Raintree Nutrition Inc., 2004;Song et al, 2007;Tabanca et al, 2006Tabanca et al, , 2007Tepe et al, 2004;Wilson et al, 1997). Thus, the compounds we identified, although not correlated with anthracnose fruit rot resistance, may play a role in resistance to other highbush blueberry fruit diseases.…”
Section: Discussionmentioning
confidence: 62%
“…The incorporation of high concentrations of various antimicrobial volatiles, including hexanal and trans-2-hexenal, into the storage atmosphere of fresh produce has been shown to reduce postharvest decay (Corbo et al, 2000;Lanciotti et al, 1999). Most, if not all, terpenes emitted from highbush blueberry have antifungal activities and include 1,8cineole Wilson et al, 1997), caryophyllene (Raintree Nutrition Inc., 2004), cadinene (Song et al, 2007), a-farnesene (Govinden-Soulange et al, 2004), 2-and 3carene (Archbold et al, 1997;Cavaleiro et al, 2006;Himejima et al, 1992), limonene (Archbold et al, 1997;Himejima et al, 1992;Wilson et al, 1997), linalool (Carson and Riley, 1995;Fraternale et al, 2004;Plotto et al, 2003), terpinolene (Himejima et al, 1992), a-terpineol (Carson and Riley, 1995;Tepe et al, 2004), and a-terpinyl acetate (Peana et al, 1999). 8-Hydroxylinalool, another volatile emitted from highbush blueberry fruit, may have antifungal activity because oxygenated terpenes generally have more antifungal activity than nonoxygenated ones (Caccioni and Guizzardi, 1994;Knobloch et al, 1989).…”
mentioning
confidence: 99%
“…In contrast, considerable differences were found to exist in the composition of essential oils of P. boivinii. The occurrence of these unusual terpenoids in these four species supposes that the latter have the same biosynthetic pathway and it may also suggest that the two new molecules could be used as a chemotaxonomic tool for the characterization of some Psiadia species (Gurib-Fakim et al, 1995Gauvin et al, 2004b;Govinden-Soulange et al, 2004;Gauvin and Smadja, 2005;Gauvin-Bialecki and Smadja, 2007).…”
Section: Chemotaxonomic Studiesmentioning
confidence: 96%